Роль поліморфізму гену інтерлейкіну-17 в розвитку змішаної кріоглобулінемії та ефективності противірусного лікування хворих на хронічний гепатит С - Калашник, Кирило Вадимович; Kalashnyk, K. V. (My University, 2019)
Abstract. The polymorphism of the IL-17 gene can affect the chronicity of hepatitis C, namely, the presence of C-alleles. Carriers of the CC genotype are more likely to detect MCG and their concentration is higher than that of carriers of CG/GG genotypes. Patients with CG/GG genotypes have been shown to be more successful in AVT. Patients who did not respond to therapy had CCgenotype, high values of activity activity and ALT concentration. Мета дослідження – визначити роль поліморфізму гену інтерлейкіну-17 (ІЛ-17) в розвитку хронічного гепатиту С, кріоглобулінемії та їх впливу на успішність противірусної терапії (ПВТ) за схемою peg-IFNα+RBV+SOF.
The role of the interleukin-17 gene polymorphism in the development of mixed cryoglobulinemia and the effectiveness of antiviral treatment of patients with chronic hepatitis C
Keywords: тези доповідей